Analysis of Student Learning Motivation In IPAS Learning With a Problem Based Approach - Sukmana, Ardian; Atmojo, Idam Ragil Widiant; Chumdari, Chumdari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Learning motivation is a crucial element that significantly influences students’ active participation and academic achievement in Natural and Social Sciences (IPAS) at the elementary school level. This study aims to analyze the learning motivation of fifth-grade students in IPAS through the application of the Problem-Based Learning (PBL) model. A qualitative approach was used with a case study design involving 26 fifth-grade students at Pandanan Public Elementary School, where data were collected through questionnaires, observations, and interviews. Data were collected through motivation questionnaires, participatory observation, and in-depth interviews, and were then analyzed thematically using the Miles and Huberman model. The results of the study showed a significant increase in intrinsic motivation, where the number of students in the “Very High” motivation category rose sharply from 3 to 12, and the “Low” motivation category disappeared. The implementation of PBL also proved to change students’ perceptions of IPAS from mere memorization to problem-solving-based learning that is more relevant and engaging. Overall, the Problem-Based Learning model proved effective and had a positive impact on improving students’ learning motivation, engagement, and the quality of their learning experiences in the IPAS subject.